Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Kasrianti; Hety Budiyanti; Nurman; Ahmad Ali; Muh. Ichwan Musa (CV. Lafadz Jaya, 2023)
This study aims to examine and analyze the factors that influence the capital structure of food and beverage subsector companies listed on the INDONESIA STOCK EXCHANGE. The technique for collecting secondary data obtained from financial data on 22 food and beverage sub-sector companies listed on the Indonesian stock exchange from 2013 to 2020, and the research sample taken is annual data for 8 years. So the amount of data obtained is 176 samples. The results of the study have been tested on classical assumptions such as the assumption of normality, the assumption of multicollinearity and the assumption of hoteroscedasticity. By applying multiple linear regression techniques in the process of analyzing the data. This study aims to examine and analyze the factors that influence the capital structure of food and beverage subsector companies listed on the INDONESIA STOCK EXCHANGE. The technique for collecting secondary data obtained from financial data on 22 food and beverage sub-sector companies listed on the Indonesian stock exchange from 2013 to 2020, and the research sample taken is annual data for 8 years. So the amount of data obtained is 176 samples. The results of the study have been tested on classical assumptions such as the assumption of normality, the assumption of multicollinearity and the assumption of hoteroscedasticity. By applying multiple linear regression techniques in the process of analyzing the data.